Serological Investigations of Bluetongue Virus (BTV) among Sheep and Goats in Kassala State, Eastern Sudan - Molhima M. Elmahi; Abdel Rahim E. Karrar; Amira M. Elhassan; Mohammed O. Hussien; Khalid A. Enan; Mohammed A. Mansour; Abdel Rahim M. El Hussein (Veterinary Medicine International)
Bluetongue (BT) is an infectious, noncontagious, vector-borne viral disease of wild and domestic ruminants. BTV is a member of the Orbivirus genus of the family Reoviridae. The present study aimed to investigate the seroprevalence of BTV in sheep and goats in Kassala State, Sudan. It also aimed to determine risk factors associated with BTV infection. The study was carried out by a structured questionnaire survey, and a total of 809 serum samples were collected from sheep (n = 459) and goats (n = 350) from 9 different localities in Kassala state. These samples were analyzed using a competitive enzyme-linked immunosorbent assay (cELISA) for the detection of BTV antibodies. The overall seroprevalence of BTV was 91.2% (738/809). In goats, the prevalence of BTV antibodies was comparatively higher (100%) than in sheep (84.5%). The prevalence differed between localities and was the highest in the center section of Kassala and Western Kassala (100%). Animals aged 6–11 months were highly infected (93.9%) compared to 1-year-old (85.5%). Caprine species was more likely to be infected (100%) than ovine (84.5%), and females were highly infected (92.8%) than males (85.5%). BTV infections were higher in the winter season (91.4%). Risk factors that showed significant associations with cELISA positivity included locality and sex (p≤0.003) and species and age (p≤0.000). Factors significantly associated with cELISA positivity in multivariate analysis were localities, species, age, and sex. BTV infection is prevalent in sheep and goat populations in Kassala state.